Trade Facilitation In ASEAN Member Countries : Measuring Progress And Assessing Priorities - Shepherd, Ben (The World Bank, 2008)
This paper reviews recent progress and indicators of trade facilitation in member countries of the Association of Southeast Asian Nations. The findings show that import and export costs vary considerably in the member countries, from very low to moderately high levels. Tariff and non-tariff barriers are generally low to moderate. Infrastructure quality and services sector competitiveness range from fair to excellent. Using a standard gravity model, the authors find that trade flows in Southeast Asia are particularly sensitive to transport infrastructure and information and communications technology. The results suggest that the region stands to make significant economic gains from trade facilitation reform. These gains could be considerably larger than those from comparable tariff reforms. Estimates suggest that improving port facilities in the region, for example, could expand trade by up to 7.5 percent or